2010
DOI: 10.1007/s00105-010-1985-9
|View full text |Cite
|
Sign up to set email alerts
|

Physikalische Lipolyse

Abstract: The number of non-invasive procedures is steadily growing. Lipolysis with focused ultrasound, cryo-lipolysis, laser-lipolysis, radiofrequency-lipolysis, HIFU-lipolysis, classic liposuction, vibration-assisted liposuction and water beam-assisted Liposuction are newly established procedures to treat diet- and sport resistant fat deposits. Non-invasive lipolysis with focused ultrasound in combination with radiofrequency as well as cryo-lipolysis are the most established procedures. The methods are described in de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…If the intervention period were longer, this study would probably obtain the same results as those in previous studies. Steinert 7 ) reported that ultrasound therapy was an effective, painless fat decomposition method and stated that it had a good effect on abdominal obesity in particular. Most secondary complications brought about by obesity are due to abdominal obesity, and ultrasound therapy is considered to positively affect obese patients who are suffering from secondary complications resulting from abdominal obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the intervention period were longer, this study would probably obtain the same results as those in previous studies. Steinert 7 ) reported that ultrasound therapy was an effective, painless fat decomposition method and stated that it had a good effect on abdominal obesity in particular. Most secondary complications brought about by obesity are due to abdominal obesity, and ultrasound therapy is considered to positively affect obese patients who are suffering from secondary complications resulting from abdominal obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, obesity management using abdominal ultrasound has been recommended in order to overcome such difficulties 6 ) . Obesity management using abdominal ultrasound is a method of reducing subcutaneous fat by decomposing it effectively into fatty acid and discharging it out of the body; recently, many relevant treatment instruments have been developed and popularized 7 ) . Accordingly, the aim of the present study was to compare ordinary complex exercise and abdominal ultrasound accompanied by complex exercise, and to present a method by which employees working in industry exposed to risk factors related to obesity can effectively overcome this disorder.…”
Section: Introductionmentioning
confidence: 99%